Methemoglobinemia: Case of Falsely low SpO2 - Srishthi Tripathy; Anmol Sharma; Robin Choudhary; Shipra Verma (Amrita Journal of Medicine, 2024)
Pulse oximetry is often regarded as the fifth vital sign. Based on the absorption of near-infrared light, any changes in the concentration of oxyhemoglobin influence the reading on the pulse oximeter. We present one such case of a 30-year-old lady with leprosy on multiple drug therapy that showed low SpO2 readings not associated with respiratory distress and did not improve with oxygenation. She was found to have dapsone-induced methemoglobinemia, which was reversed after 48 h of stopping the drug intake.